Performance of Ultrasonography Compared to Conventional Radiography for the Diagnosis of Osteoarthritis in Patients With Knee Pain - Brom, Martin; Gandino, Ignacio J.; Zacariaz Hereter, Johana B.; Scolnik, Marina; Mollerach, Florencia B.; Ferreyra Garrott, Leandro G.; Marin, Josefina; Ruta, Santiago O.; Rosa, Javier E.; García-Mónaco, Ricardo D.; Soriano, Enrique R. (Frontiers in Medicine, 2020)
Purpose: To investigate the performance of US for the detection of knee OA in patients suffering from knee pain, compared to the conventional radiographs. 1 Methods Cross-sectional study performed at a university teaching hospital. Consecutive patients complaining of unilateral or bilateral mechanical knee pain who signed an informed consent were included. All patients underwent simultaneously an ultrasonographic and a radiographic evaluation of the knee. Exclusion criteria were age under 18 years, prior diagnosis of knee OA, diagnosis of inflammatory arthritis, history of knee surgery or trauma, severe knee deformities and corticosteroid injection within the last 2 months The diagnostic properties of US for the detection of knee OA were evaluated using radiological data as the reference method. Evaluated test properties were sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and the positive and negative likelihood ratio (LR+ and LR-). 2 Results Three-hundred twenty-two knees (281 patients) were included. Radiographic degenerative changes were present in 56.8% (183) of the evaluated knees. Regarding the diagnostic properties of the US, the presence of either osteophytes or the compromise of the femoral hyaline cartilage had the best sensitivity to detect OA (95%), with a NPV of 92% and a LR- of 0,07, and the identification of osteophytes had the best specificity (86%), with 89% PPV and a LR+ of 5,85. 3 Conclusion US demonstrated an excellent sensitivity with an adequate specificity for the detection of radiographic knee OA.